(untitled) (Al-Qamar, 2024)
Rhetoric refers to the use of language in speech or writing, especially in speech, with both external and internal qualities. This is such a miraculous aspect of the Qur’an, without the understanding of which it becomes impossible to reach the real meaning and purpose of the divine word. That is why the commentators of every age have adopted the style of rhetorical explanation of the Qur’anic verses while interpreting the Qur’an."Al-Tahrir wa al-Tanwir" is one such rhetorical commentary of the 20th century in which Allama Muhammad al-Tahir Ibn Ashoor has shed light on the rhetorical aspect of the verses in great detail. Therefore, in this article, the rhetorical method of Allama ibn Ashoor’s commentary "Al-Tahrir wa al-Tanwir" is presented.